Potential and Limitations of Cross-Protective Vaccine against Malaria by Blood-Stage Naturally Attenuated Parasite - Takashi Imai; Kazutomo Suzue; Ha Ngo-Thanh; Chikako Shimokawa; Hajime Hisaeda (Vaccines, 2020)
Human malaria vaccine trials have revealed vaccine efficacy but improvement is still needed. In this study, we aimed to re-evaluate vaccination with blood-stage naturally attenuated parasites, as a whole-organism vaccine model against cross-strain and cross-species malaria, to establish a better vaccination strategy. C57BL/6 mice controlled blood-stage Plasmodium yoelii 17XNL (PyNL) within 1 month of infection, while mice with a variety of immunodeficiencies demonstrated different susceptibilities to PyNL, including succumbing to hyperparasitemia. However, after recovery, survivors had complete protection against a challenge with the lethal strain PyL. Unlike cross-strain protection, PyNL-recovered mice failed to induce sterile immunity against Plasmodium berghei ANKA, although prolonged survival was observed in some vaccinated mice. Splenomegaly is a typical characteristic of malaria; the splenic structure became reorganized to prioritize extra-medullary hematopoiesis and to eliminate parasites. We also found that the peritoneal lymph node was enlarged, containing activated/memory phenotype cells that did not confer protection against PyL challenge. Hemozoins remained in the spleen several months after PyNL infection. Generation of an attenuated human blood-stage parasite expressing proteins from multiple species of malaria would greatly improve anti-malaria vaccination.